Effects of ENSO on Autumn Rainfall in Central Vietnam - Thang Van Vu; Hieu Trong Nguyen; Thang Van Nguyen; Hiep Van Nguyen; Huong Thi Thanh Pham; Lan Thi Nguyen (Advances in Meteorology)
28 years (1980–2007) of station and gridded reanalysis data were used to investigate the effects of El Niño/Southern Oscillation (ENSO) on autumn rainfall in the Extended Central Vietnam (ECV) region. Results show that, under El Niño conditions, autumn rainfall in Central Vietnam is reduced by about 10 to 30%. This reduction seems to be caused by a weakening of the North East monsoon circulation, which appears to be linked to an anomalous anticyclonic vortex and a positive sea level pressure anomaly over the East Sea. In addition, the disappearance of a secondary moisture source over the southern region of the East Sea also favors the reduction in rainfall over this region. Conversely, during La Niña, the total autumn rainfall in the ECV region increases by about 9 to 19%. The strengthening of the North East monsoon, with a cyclonic wind anomaly over the East Sea, helps to increase the moisture supply to the area by about 10 to 20%, resulting in enhanced rainfall in the ECV. It is also found that the La Niña conditions do not only cause an increase in rainfall, but also change the temporal distribution of the monthly rainfall over the region, with more rainfall in the latter months of the year.